Understanding Li‐Ion Dynamics in Lithium Hydroxychloride (Li2OHCl) Solid State Electrolyte via Addressing the Role of Protons. Issue 8 (17th January 2020) - Song, Ah‐Young; Turcheniuk, Kostiantyn; Leisen, Johannes; Xiao, Yiran; Meda, Lamartine; Borodin, Oleg; Yushin, Gleb
Abstract: Low‐melting‐point solid‐state electrolytes (SSE) are critically important for low‐cost manufacturing of all‐solid‐state batteries. Lithium hydroxychloride (Li2 OHCl) is a promising material within the SSE domain due to its low melting point (mp < 300 °C), cheap ingredients (Li, H, O, and Cl), and rapid synthesis. Another unique feature of this compound is the presence of Li vacancies and rotating hydroxyl groups which promote Li‐ion diffusion, yet the role of the protons in the ion transport remains poorly understood. To examine lithium and proton dynamics, a set of solid‐state NMR experiments are conducted, such as magic‐angle spinning 7 Li NMR, static 7 Li and 1 H NMR, and spin‐lattice T 1 ( 7 Li)/ T 1 ( 1 H) relaxation experiments. It is determined that only Li + contributes to long‐range ion transport, while H + dynamics is constrained to an incomplete isotropic rotation of the OH group. The results uncover detailed mechanistic understanding of the ion transport in Li2 OHCl. It is shown that two distinct phases of ionic motions appear at low and elevated temperatures, and that the rotation of the OH group controls Li + and H + dynamics in both phases. The model based on the NMR experiments is fully consistent with crystallographic information, ionic conductivity measurements, and Born–Oppenheimer molecular dynamic simulations. Abstract : Lithium hydroxychloride is an attractive solid electrolyte, in which ion transport mechanism should be experimentally identified. In addition to Born–Oppenheimer molecular dynamics, solid‐state nuclear magnetic resonance studies are reported and mechanistic insights on Li + transport from their original site to a destination site by using a rotation of proton in OH group are described.